IRANIAN PAYMENT SYSTEM “SHETAB” AND PROSPECTS OF THE IRANIAN BANK CARD SYSTEM IN FOREIGN COUNTRIES - M. M. Rahimian (Вестник университета)
Since the imposition of sanctions on the Republic of Iran, no international payment system has been established in the country. As a result, Iran implemented a solution to the described problems without attracting external assistance, in particular, the Shetab payment system was created and its connection to ATM networks in Bahrain, Qatar, the UAE and Kuwait was implemented. Iran also introduced the Shetab Bank card system, which is extended to Armenia and Turkey. The impact of bilateral payment system on economic growth and increase in cash turnover between two countries, during the period of economic sanctions, has been considered in the article.